The effects of personal characteristics on employee voice behaviors: The moderating effects of organizational trust - Kwon, Nuri; Tak, Jinkook (Korean Journal of Industrial and Organizational Psychology, 2015)
The purpose of this study was to examine the validity of four different types of voice behavior developed by Maynes and Podsakoff(2013). In addition, relation of personal characteristics to four different types of voice behavior and moderating effects of organization trust on relationship between personal characteristics and voice behavior were examined. Data were obtained from 309 employees in various organizations in Korea. Results showed that proactive personality was positively influences constructive voice and negatively influences destructive voice. Also psychological collectivism was positively influences supportive voice, and trait cynicism was positively influences defensive voice and destructive voice. The results of hierarchial regression analyses showed that organization trust moderated the relationship between psychological collectivism and supportive voice, defensive voice. Finally, the implications and limitations of this study and the directions for future research were discussed.